A Study on Internet Banking Adoption among Bank Customers - Mohd Najmie, Haji Osman (2009)
The online banking environment has grown tremendously over the past several years and will continue to grow as financial institutions continue to strive to allow customers to complete money transfers, pay bills and access critical information online. At the same time,online banking has been plagued by internet criminals and fraudsters attempting to steal customer information . The primary purpose of this study is to identify factors that induced consumers to adopt the internet banking services. A total of 160 respondents are involved in this study. The effects of attitude towards certain behaviors, subjective norm and perceived behavioral control variables on the intention to use online financial services were examined as well as demographic variables. The conceptual framework underlying the study was based combination of different scholar that is relevant internet banking adoption. The findings based on five different independent variables (Banking Needs, Costs Saved, Risk and Privacy, Features Availability and Convenience)showed that all these variables influenced consumers’ internet banking adoption. It is essential for banks to facilitate encouragement and restrict impediment factors. The results suggest that in addition to the direct “push” from banks (in respect of the encouragement factors), indirect persuasion should also be carried out as a “pull” mechanism (in respect of the impediment factors) to induce consumers participating in the internet banking services.